Antony Holland presents Shakespeare - Holland, Antony; Inside Edge Films Inc. (Canada : Inside Edge Films Inc., 2004)
The video includes Holland performing in an intimate setting and interview clips where he discusses techniques for actors and directors. at 86 years young, Holland brings energy and intensity to a one-man show that is simply a joy to watch
Part 1, 2 and 3
Presenter : Antony Holland
Keywords: Shakespeare, William, -- 1564-1616